2009
DOI: 10.1016/j.bpj.2009.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Silent Divalent Cation Entries in Resting and Active Voltage-Controlled Muscle Fibers

Abstract: Ca2+ is known to enter skeletal muscle at rest and during activity. Except for the well-characterized Ca2+ entry through L-type channels, pathways involved in these Ca2+ entries remain elusive in adult muscle. This study investigates Ca2+ influx at rest and during activity using the method of Mn2+ quenching of fura-2 fluorescence on voltage-controlled adult skeletal muscle cells. Resting rate of Mn2+ influx depended on external [Mn2+] and membrane potential. At -80 mV, replacement of Mg2+ by Mn2+ gave rise to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
4
28
2
Order By: Relevance
“…Thus Ca 2ϩ ceased to enter dystrophic (or healthy) muscle via the SOCE pathway once the store refilled to its full deactivation threshold and did not comply with a deregulated SOCE complex (5). While the skinned fiber preparation we have used for our experiments does not have a sarcolemma, therefore excluding potential store-dependent Ca 2ϩ influxes, recent experimental evidence suggests that there is no functional SOCE across this membrane anyway (1,4). Indeed, the SR is separated from the sarcolemma by the subsarcolemmal space (10), making any form of coupling between the sarcolemma and SR a longdistance affair.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus Ca 2ϩ ceased to enter dystrophic (or healthy) muscle via the SOCE pathway once the store refilled to its full deactivation threshold and did not comply with a deregulated SOCE complex (5). While the skinned fiber preparation we have used for our experiments does not have a sarcolemma, therefore excluding potential store-dependent Ca 2ϩ influxes, recent experimental evidence suggests that there is no functional SOCE across this membrane anyway (1,4). Indeed, the SR is separated from the sarcolemma by the subsarcolemmal space (10), making any form of coupling between the sarcolemma and SR a longdistance affair.…”
Section: Discussionmentioning
confidence: 96%
“…Allard et al (1) followed this work using similar electrophysiological techniques but could not record a store-dependent current across the sarcolemma at 2.5 mM Ca 2ϩ . Using a combined electrophysiology and fluorescence experimental approach, the same group recently confirmed that SOCE indeed occurs across the tubular (t-) system and not sarcolemma (4). Moreover, the second study of SOCE in dystrophic muscle measured SOCE under conditions of chronic long-term SR depletion, a condition that never occurs in muscle or during depolarization (5), which does not allow isolation of the store-dependent influx.…”
mentioning
confidence: 99%
“…We previously showed in adult mouse muscle fibers that sarcoplasmic reticulum (SR) Ca 2ϩ depletion failed to induce any increase in the resting whole-cell conductance and inward single channel activity (10). We also demonstrated that the resting and store-operated Ca 2ϩ entries detected by the Mn 2ϩ quenching method did not produce any measurable macroscopic current in adult muscle cells (11). If TRPC1 is actually involved in Ca 2ϩ influx, our results suggest that the ion current generated by TRPC1 activity is too minute to be resolved, or, alternatively, that TRPC1 channel is not active in the plasma membrane and indirectly influences plasmalemmal Ca 2ϩ influx.…”
mentioning
confidence: 99%
“…In a subsequent study not related to SOCE, the same author(s) recently showed that membrane Ca 2+ flux determined by Mn 2+ quenching in adult fibers crucially depends on the membrane potential and the Mn 2+ concentrations used (Berbey and Allard 2009). This has to be kept in mind, as most studies on SOCE detected by Mn 2+ quench did not keep divalent ion concentrations constant (Hopf et al 1996;Boittin et al 2006;Zhao et al 2006).…”
Section: Store-operated Ca 2+ Entry (Soce) In Skeletal Musclementioning
confidence: 99%
“…The authors also gave several more reasons to explain these controversial results that are summarized in their work (Bannister et al 2009) and in Dirksen (2009). On the other hand, there is recent experimental evidence that a channel or transporter distinct from the DHPR could mediate the ECCE current in addition to the DHPR, as the activation curves for Mn 2+ influx were shifted towards more negative potentials compared to the respective curves for L-type currents (Berbey and Allard 2009). In summary, the question about the molecular identity of the ECCE pathway remains unanswered.…”
Section: Excitation-coupled Ca 2+ Entry (Ecce) In Skeletal Musclementioning
confidence: 99%